Pulmonary vein mass with extension to the left atrium diagnosed by echocardiography - Taquiso, Jezreel Labrador (BMJ Case Rep, 2017)
We report a case of a man aged 65 years presenting with chronic cough, haemoptysis and intermittent atrial tachyarrhythmias on ECG. On 2D transthoracic echocardiography, an incidental left atrial mass was seen, initially thought to be a thrombus predisposed by intermittent atrial fibrillation. Transoesophageal echocardiography confirmed that this left atrial mass originated from a fixed, non-homogenous, right superior pulmonary vein mass with an extracardiac extension. Because of this finding, a thorough search for a primary focus lead to the discovery of a contiguous posterior mediastinal mass, which was a round cell neoplasm on histology. Management was deemed palliative. Although rare, left-sided cardiac masses should prompt the physician to search for a malignancy in the lung in high-risk patients, as haematogenous spread via the pulmonary vein is a potential mechanism for spread.